Application of five seismic attributes in natural fracture prediction for deep coalbed methane production along the eastern margin of the Ordos Basin - Jiangnan TONG; Feng WANG; Feng ZHANG; Wei HOU; Zhongbai LI; Liang JI; Yanan JIANG; Wei SUN (Meitian dizhi yu kantan)
BackgroundNatural fractures serve as both the primary storage space for free gas of deep coalbed methane (CBM) and pathways for hydrocarbon migration. Furthermore, these fractures can enhance the porosity and permeability of strata under the deep, high-pressure condition, significantly amplifying the permeability of coal seams. Therefore, the fine-scale characterization of the planar distribution of natural fractures is crucial to deep CBM production.Objectives and MethodsThis study investigated the No.8 coal seam in the Carboniferous Benxi Formation within the Daning-Jixian block on the eastern margin of the Ordos Basin. Through offset vector tiles (OVT) domain processing of offshore 3D wide-azimuth, broadband, and high-density (WBH) seismic data, this study determined five-dimensional seismic data: time, space (3D coordinates), offset (or shot-to-geophone distance), and azimuth. Then, fracture prediction was conducted through a pre-stack analysis of the azimuthal anisotropy attributes. Results and Conclusionsthis study developed a technical process for the five-dimensional seismic data-based interpretation that combined the methods of elliptical fitting and azimuthal statistics. The results reveal the presence of conjugate fracture systems in the study area: Yanshanian nearly EW/NEE- and Himalayan nearly SN/NNE-oriented fractures. The verification using multi-source data, including formation micro-imaging (FMI) logs, array acoustic logs, and fracturing curves, indicates that the azimuthal statistical method exhibited higher reliability in predicting fracture orientation (coincidence rate: 89 %) and developmental degree (prediction accuracy: 88.5 %). The results of this study have provided successful guidance for the optimization of horizontal well deployment, providing significant technical support for the efficient development of deep CBM. The relevant methodology can be widely applied to other basins bearing deep coal-bearing gas.